IMPLEMENTASI KONSELING INDIVIDU PENDEKATAN SOLUTION FOCUSED BRIEF COUNSELING TEKNIK EXCEPTION QUESTION UNTUK MENINGKATKAN SELF-ACCEPTANCE - Risma Kumara Rani; Riska Andriani; Khayatun Nufus Akhsania; Syifa Jauhar Nafisah; Susi Handayani Boru Lubis (UNMUHBABEL Press, 2025)
This study aims to describe the results of the implementation of individual counseling services with the Solution Focused Brief Counseling (SFBC) approach using the Exception Question technique in improving self-acceptance in students. The method used is action research with two service cycles which are complemented by observation, interviews, and questionnaires. The results showed that the SFBC approach was effective in helping students recognize their potential and positive experiences, so as to increase self-acceptance. The counseling process includes extracting moments when problems occur, setting goals, reflection, and giving practical assignments. Although there are obstacles such as limited space and inconsistent schedules, in general, this counseling service shows a positive impact. In conclusion, individual counseling with the SFBC (Solution Focused Brief Counseling) approach with Exception Question technique is an effective strategy in improving students' self-acceptance in the school environment.